2022
DOI: 10.1177/00307270221144641
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence the likelihood of rural farmer participation in digital agricultural services? experience from smallholder digitalization in Northern Ghana

Abstract: Participation in digital services is critical for the inclusiveness of digitalization in smallholder Africa. However, farmers engagement with digitalization services needs further explorations due to limited empirical research on the topic. This paper thus employs a cross-sectional survey of 1565 farmers in Northern Ghana to assess the factors that affect the likelihood of farmers’ participation in digital agricultural services. We applied a polynomial regression model to show that gender, affiliations to farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
0
17
0
3
Order By: Relevance
“…1 ) highlights that, by influencing access to and utilization of these livelihood assets in the pursuit of livelihood strategies, the integration of digital technology in agriculture integration can result in positive livelihood outcomes (i.e. reduced vulnerability, improved income, adequate health and well-being, food security and more sustainable use of resources) [ [28] , [29] , [30] , [31] , [32] ].…”
Section: Conceptual Linkages Between Agricultural Digitalization and ...mentioning
confidence: 99%
“…1 ) highlights that, by influencing access to and utilization of these livelihood assets in the pursuit of livelihood strategies, the integration of digital technology in agriculture integration can result in positive livelihood outcomes (i.e. reduced vulnerability, improved income, adequate health and well-being, food security and more sustainable use of resources) [ [28] , [29] , [30] , [31] , [32] ].…”
Section: Conceptual Linkages Between Agricultural Digitalization and ...mentioning
confidence: 99%
“…As reviewed earlier, adoption of digital agricultural technologies is likely associated with demographic, socio-economic, situational and institutional factors. Previous research has revealed that different farmers have a different adoption of digital agricultural technologies (Abdulai et al, 2023; Ammann et al, 2022; Giua et al, 2022; Larson et al, 2008; Michels et al, 2019; Pfeiffer et al, 2021; Pivoto et al, 2019; Silva et al, 2011; Tamirat et al, 2018). As shown in Figure 1, the dependent and explanatory variables are associated with an arrow revealing that the dependent variable (adoption of digital agricultural technologies) is affected by the explanatory variables.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A number of research into farmers’ adoption of digital technologies in agriculture has been carried out in other countries (Abdulai et al, 2023; Ammann et al, 2022; Giua et al, 2022; Larson et al, 2008; Michels et al, 2019; Pfeiffer et al, 2021; Pivoto et al, 2019; Silva et al, 2011; Tamirat et al, 2018). The mainstream literature shows that the farmer's use of digital technologies is likely to be influenced by the following factors: (A) demographic characteristics of farmers such as age, gender and education levels (Ammann et al, 2022; Gyawali et al, 2023; Pfeiffer et al, 2021), (B) characteristics of farms and households such as farming experience, farm size and income (Barnes et al, 2019; Marescotti et al, 2021), (C) situational factors such as distance from nearest markets (Abebe and Mammo Cherinet, 2019) and (D) institutional characteristics such as farmers’ participation in workshops and cooperatives (Pivoto et al, 2019; Tamirat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such investment is central to closing the yield gaps for most of the region's staple food crops, considered food security crops. Further, SFA, in some contexts, could also mean enhancing access to digital agriculture technologies, which will help farmers be precise with input applications and adapt well to both climate and non-climatic stressors while drastically reducing agriculture's contribution to global GHGs emissions (e.g., Abdulai, 2022aAbdulai, , 2022bAbdulai et al, 2023;Duncan et al, 2021;Green et al, 2021). Where possible, novel food production frontiers, such as aquaculture, seaweed, and so forth, could be expanded to address food security and climate adaptation needs (Glaros et al, 2021).…”
Section: 4mentioning
confidence: 99%